The Druid Animal Oracle: o jogo divinatório como reflexo de uma sociedade bricolada - Mendonça, Bárbara Matte de Fernandes (2023)
We can observe Druidry from different perspectives. In this study, based on the observation and analysis of cards from the oracle linked to the Order of Bards, Ovates and Druids (OBOD), The Druid Animal Oracle, we aim to delimit the main sources of inspiration for fomenting neo-druidic beliefs, whether those of historical origin, such as the reports of Romans and Greeks, or from the Irish and Welsh vernacular tradition. Using the concepts of bricolage, Material Religion and the New Age ethos, we intent to create the scenario of how it is possible, from an object, to delimit part of a religious system